Hearing preservation with a slim modiolar cochlear implant in a pediatric cohort. (January 2021) - Jimenez, Joaquin E.; Govil, Nandini; Shaffer, Amber D.; Ledonne, Jessica C.; Chi, David H.
Abstract: Objectives: Recent cochlear implant (CI) electrodes are designed to be atraumatic to inner ear structures. Studies in adults have demonstrated improved hearing preservation rates with the CI532/632 electrode, but none have examined this in children. Our objective is to describe the hearing preservation rate with CI532/632 in pediatric patients and determine factors that influence hearing preservation. Methods: We conducted a retrospective cohort study of children undergoing CI over a three-year period. Inclusion criteria were: CI with the 532/632 electrode, presence of pre-operative low frequency hearing defined by pure tone average (PTA) of ≤80 dB at 250 Hz or at the average of 250 and 500 Hz, and post-operative unaided audiometry. Other data collected included demographics, otologic history, imaging, and surgical details. Results: A total of 13 patients and 15 ears were included. Hearing was preserved in 10/15 (66%) ears at an average follow-up of 6 months, similar to that reported in the adult literature. Patients with preserved hearing post-operatively were more likely to have a positive family history of hearing loss. There was a trend towards patients with anatomic inner ear abnormalities being more likely to lose hearing after CI, but this was not statistically significant. Pre-operative thresholds were not predictive of hearing preservation. Patients with preserved hearing had a significantly smaller shift in thresholds after cochlear implantation. Therefore, hearing preserved and non-preserved groups differed more by the magnitude of change in threshold, rather than their preoperative threshold. Other factors such as age, sex, surgeon, and surgery duration were not associated with hearing preservation. Conclusion: This study describes low frequency hearing preservation after pediatric CI532/632 implantation. The hearing preservation rate in our cohort was consistent with that reported in the adult literature. Our data suggest that preoperative thresholds do not solely determine which patients will go on to experience hearing preservation. We believe this will aid surgeons with patient-specific device selection and counseling potential pediatric CI recipients with preserved hearing. Highlights: Hearing preservation rate in this pediatric cohort was 66% with CI532/632. Comparable to reports in adults with perimodiolar and lateral wall implants. Anatomic inner ear abnormalities may confer higher risk of residual hearing loss. Pre-operative thresholds are not strongly associated with hearing preservation.